Depression Among Rural Aged : Facts & Reasons - Rahman, Md Mahfuzar; Rahman, Md Atiqur; Sajani, Tabassum Tahmin (Anwer Khan Modern Medical College Journal, 2017)
Background: In Bangladesh person aged 60 years or above are considered to elderly. 5.9% of total population are within the age group of 55-65years and 65 years old or above are 5% of the total population. Elderly dependency ratio is 7.3%. Depression is a common problem among the older people, but it is not a normal part of aging. The aim of this study was to find out the level of depression, factors associated with depression and health problems among the respondents . Material and Methods: This descriptive cross sectional study was carried among 829 people aged more than 60 years by purposive sampling technique from 7th to 9th December, 2014 in different vilages of Dhamrai Upazila,Dhaka. Data were collected on a pretested questionnaire by face to face interview using short form of GDS. Data were analyzed manually and by using computer. Results: Then study revealed that majority of the respondents (82%) were Muslims by religion. About 39% respondents were aged more than 70 years and mean age was 68±3.7 years. Most of them (52%) were illiterate and only 5% had received HSC or higher education. About 15% respondents' occupation were service and 47% of the respondents were housewives. Among all the respondents about 22% & 26% were found to have 2& 3 number of children respectively. About 27% & 18% respondents were suffering from mild & moderate depression respectively. Feeling burden on others, physical disability, lack of close family ties & Living alone were found the main factors of depression in 27%, 26%, 26% & 22% respondents respectively. About 59%, 57%, 49% & 28% respondents were suffering from poor vision, musculo-skeletal diseases, hypertension & chest pain respectively. Conclusion: Elderly people are suffering from various health problems due to depression. The study findings demand awareness among family members as well as an establishment of comprehensive one stop health care delivery package for the senior citizens. Anwer Khan Modern Medical College Journal Vol. 6, No. 2: July 2015, P 20-24